VARIABILITY OF URINE PARAMETERS IN CHILDREN INFECTED WITH SCHISTOSOMA HAEMATOBIUM IN UKAWU COMMUNITY, ONICHA LOCAL GOVERNMENT AREA, EBONYI STATE, NIGERIA - Elom, Juliana Eze; Odikamnoro, Oliver O.; Nnachi, Agwu Ulu; Ikeh, Ifeanyi; Nkwuda, John O. (African Journal of Infectious Diseases (AJID), 2017)
Background: Schistosomiasis, a chronic, debilitating and neglected tropical and sub-tropical water-borne ailment, ishighly endemic in Nigeria, especially among primary school children in rural communities. The study on the variabilityof urine parameters in children infected with Schistosoma haematobium in Ukawu community, Onicha LocalGovernment Area of Ebonyi State, was undertaken.Materials and Methods: Urine samples were aseptically collected from 400 primary school children in the communityand analysed using chemical reagent strips and sedimentation techniques.Results: The study revealed an overall prevalence of 27% as 108 pupils out of 400 were infected with S. haematobiumin the area. Proteinuria, haematuria and leucocyturia were observed to occur in 67.0%, 79.0% and 74.9% respectively.Males had higher infections and higher occurrences of proteinuria, haematuria and leucocyturia (72.5%, 88.2% and82.4% respectively). There was no significant difference with respect to sex (P<0.05). Children within ages 12-15 yearshad the highest prevalence of S. haematobium (35.5%) while those within the ages of 4-7 had the least prevalence(11.4%). The difference in the rate of infection between the different age groups was significant, statistically (P>0.05).Children within ages 12-15 had the highest occurrence of proteinuria, haematuria and leucocyturia while childrenwithin ages 4-7 had the least occurrence of the three urine parameters. All the pupils excreting above 40 egg/10ml ofurine had proteinuria, haematuria and leucocyturia.Conclusion: The study revealed that the community studied is endemic with Schistosoma haematobium infections andthe level of the urine parameters increased with the intensity of infection. Prompt case detection and treatment, goodpersonal hygiene, eradication of snail hosts, public enlightenment and proper waste disposal are hereby recommended.